Taking the commanding heights : BNBM's branding strategy - Yu, Chungling; Mao, Chuanjiang (London : Tsinghua University School of Economics and Management, 2017)
BNBM is a state owned Chinese enterprise that manufactures Gypsum boards for the construction industry. This case examines how the brand management of BNBM and how this contributed to BNBM's sales growth.
Originally Published InYu, C., & Mao, C. (2017). Taking the Commanding Heights: BNBM's Branding Strategy. 8-817-312. Beijing, China: Tsinghua SEM Chinese Business Case Center.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Bei xin jian cai (ji tuan) you xian gong si (China) -- Case studies; Product management -- China -- Beijing -- Case studies; Branding (Marketing) -- Case studies